Koszt wytworzenia produktu jako czynnik kształtujący wielkość odpisu aktualizującego z tytułu utraty wartości przez produkty gotowe - Szydełko, Alfred (Cost of Product Manufacturing as a Factor which Affects the Valuation Allowance Caused by Depreciation of Inventory, 2005)
The proper determination of cost of product manufacturing influences the correct appraisal of them, and consequently the proper determination of financial result. While determining the cost of manufacturing one should pay attention to the aspect of grouping and calculating indirect costs of products manufacturing, and especially to the procedures of isolating the changeable costs and justified overheads. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 282-288